PC Remote Control - Titi, Ahmad; Sharawneh, Amane (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2023)
This project aims to design an infrared remote control that controls the PC, it was found as an alternative for Keyboard and Mouse in some cases. With the remote, you have full control over the PC, you can control the mouse and move it in all directions, and you can open any application, increase or decrease the volume, or even shut the computer down using the remote. We will assign a task for each button and explain it in later sections of the document. The project requires an Infrared remote, infrared receiver, Arduino Nano, ESP32, and a gyroscope. It’s planned that the Infrared receiver will be connected to the Computer directly using a USB cable, and the Air Mouse (ESP32 & Gyroscope MPU6050) will be connected to the PC through a Bluetooth adapter. Note that the system will be designed for LG Infrared remotes. Any other brands can be programmed to control the PC, but in our system we’re planning to program an LG remote.
no of pages 57, هندسة حاسوب 4/2023
Keywords: PC Remote Control